High-entropy carbide combined polycrystalline cubic boron nitride and preparation method thereof

By adopting high-entropy carbide ceramic bonding agent and high-temperature and high-pressure sintering technology, polycrystalline cubic boron nitride combined with high-entropy carbide was prepared, which solved the problem of insufficient hardness and thermal stability of PcBN materials during high-temperature cutting and long-term dry turning, and achieved higher service life and production efficiency.

CN119751082APending Publication Date: 2025-04-04YANSHAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510037249.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing polycrystalline cubic boron nitride (PcBN) materials have insufficient hardness and thermal stability during high-temperature cutting and long-term dry turning, resulting in short tool service life and low production efficiency.

Method used

High entropy carbide ceramic bonding agents, including TiC/VC/ZrC/NbC/Mo2C/HfC/TaC/WC/TiN0.3/TiB1.8/Al/ZrO2, were prepared by mechanical alloying and ball milling, combined with high-temperature and high-pressure sintering technology.

Benefits of technology

It improves the high-temperature cutting hardness and thermal stability of PcBN, realizes long-term dry turning, extends the service life of the tool, and improves the production efficiency of the enterprise.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to high-entropy carbide combined polycrystalline cubic boron nitride and a preparation method thereof, the raw materials comprise cubic boron nitride (cBN) and TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN0.3 / TiB1.8 / Al / ZrO2 (HEC) powder, the volume percentage of the cBN is 80-95%, and the balance is the HEC powder. During preparation, the cBN powder and the HEC powder are mixed according to different proportions and then are pre-pressed, the pre-pressing pressure is 400 MPa, and the pre-pressing time is 100 s. And then carrying out high-temperature and high-pressure sintering on the pre-pressed sample. The sintering pressure is 6 GPa, the sintering temperature is 1500-1800 DEG C, the heat preservation time is 10 min, then cooling and pressure relief are conducted, and the high-entropy carbide combined polycrystalline cubic boron nitride is prepared. The high-entropy carbide is used as a binding agent of the PcBN, the high-entropy carbide ceramic becomes the PcBN with good thermal stability and excellent performance by using the thermodynamic stability and the stable mechanical property at high temperature of the high-entropy carbide ceramic, and high hardness and good fracture toughness are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to high-entropy carbide-bonded polycrystalline cubic boron nitride and a preparation method thereof. Background Art

[0002] Polycrystalline cubic boron nitride (PcBN) not only retains the advantages of cubic boron nitride (cBN) such as high hardness, high wear resistance and stability, but also overcomes its single cleavage brittleness. Therefore, it has been effectively positioned as the preferred tool material in hard machining applications and is widely used in many fields such as aerospace, automobiles, bearing processing, and heavy industry. The binder is a bridge that bonds cBN particles. Its appropriateness is directly related to the performance of PcBN materials. The binder of PcBN can be divided into three types in production and research, namely metal binder, ceramic binder and metal ceramic binder.

[0003] Xu Shuai et al. used non-stoichiometric titanium nitride (TiN X , 0.3 ≤ X ≤ 0.6) as the basic component of the binder in the cubic boron nitride polycrystalline composite material, and one or two of aluminum nitride (AlN) and titanium carbide (TiC) as the binder component, and cubic boron nitride single crystals are sintered at high temperature and high pressure to prepare cubic boron nitride polycrystalline composite materials, wherein the pressure is 4-6.5 GPa, and heated to 1400-1650 ℃, and maintained at this pressure and temperature for 1-25 minutes. The advantage is that there is no single element or alloy phase in PcBN, avoiding the existence of soft spots, and the hardness of the obtained cubic boron nitride polycrystalline composite material reaches 38-55 GPa, and the fracture toughness reaches 3.31-4.12 MPa·m 1 / 2 . [Wang Mingzhi, Zou Qin, Zhao Yucheng, et al. Method for preparing polycrystalline diamond from nano-onion-carbon + micron diamond: CN103274398A. Yanshan University, published on September 4, 2013] Zou Qin et al. used aluminum powder, nickel powder, copper powder, chromium powder, and iron powder as raw materials to prepare PcBN combined with high entropy alloy, which improved the high temperature stability of the binder. At the same time, the preparation conditions of polycrystalline cubic boron nitride materials are mild, the process operation is simple, and the reaction process is easy to control. The prepared PcBN has high hardness and strength, which greatly improves the performance. Zou Wenjun et al. used the introduction of Si3N4 whiskers and Si3N4 whiskers coated with nano-nickel on the surface to increase the toughness of the PCBN composite sheet and improve the impact resistance of the PCBN tool, thereby achieving long-term continuous turning, improving the practical life of the tool and the production efficiency of the enterprise. The processing range of the polycrystalline cubic boron nitride (PCBN) tool is relatively wide, and can be used in advanced CNC machine tools, multi-purpose automatic Machine tools and special high-speed automatic line machine tools, as well as flexible production systems used in processing hardened steel, chilled cast iron, die steel and hardened forged steel parts. Summary of the invention

[0004] The present invention uses a mechanical alloying method to ball mill the binder powder TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN 0.3 / TiB 1.8 / Al / ZrO2, the ball milling time is 12~30 h, then 80%~95% of cBN particles are added and mixed evenly, and the mixture of binder and cBN is sintered at high temperature and high pressure (6GPa / 1500~1800℃ / 10~20 min) to prepare high entropy carbide-bonded polycrystalline cubic boron nitride.

[0005] Furthermore, high entropy ceramic binder powder TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN 0.3 / TiB 1.8 / Al / ZrO2 was synthesized by mechanical alloying with an equimolar ratio of transition metal atoms and a ball milling time of 12 h.

[0006] Furthermore, the cBN particles have different cBN volume proportions of 95%, 90%, 85%, and 80%, and the corresponding cBN particle sizes added are 1 μm, 2 μm, 4 μm, and 8 μm, respectively.

[0007] The present invention also discloses a method for preparing high entropy carbide-bonded polycrystalline cubic boron nitride, which comprises the following steps: S1, binder powder TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN 0.3 / TiB 1.8 / Al / ZrO2 mechanical alloying, according to the transition metal in an equal molar ratio, weigh a total of 10 g of powder; the powder is ball-milled using a planetary ball mill, the ball mill and grinding balls are made of tungsten carbide, the ball-to-material ratio is 20:1, before ball milling, the weighed raw materials and grinding balls are placed in the ball mill in the argon atmosphere (99.99%, 0.5 MPa) of the glove box; the mass ratio of large, medium and small grinding balls is 5:3:2, and the diameters are 10 mm, 5 mm, and 1 mm respectively; in the glove box, add 1 ml of industrial alcohol as a dispersant to the powder, seal the ball mill, and fill it with argon atmosphere. The ball milling parameters are set as follows: speed 450 r / min; time 12 h; S2. The high entropy carbide powder after mechanical alloying is mixed evenly with cBN in a volume ratio of 20~5%:80~95%. According to different cBN volume proportions of 95%, 90%, 85%, and 80%, the corresponding cBN particle sizes are 1μm, 2μm, 4μm, and 8μm, respectively. After the mixing is completed, pre-pressing is carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample is sintered at high temperature and high pressure. The sintering pressure is 6 GPa, the sintering temperature is 1500~1800 ℃, the holding time is 10 min, and then the temperature is reduced and the pressure is released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0008] Furthermore, according to different cBN volume proportions of 95%, 90%, 85%, and 80%, and different sintering temperatures of 1500~1800℃, the hardness of the obtained polycrystalline cubic boron nitride is 21~33 GPa, and the fracture toughness is: 6~9.1 MPa·m 1 / 2 .

[0009] Furthermore, first, a pressure of 6 GPa is slowly applied to the sample within 1 minute; then the temperature is raised to 1500~1800 ℃ and kept warm for 10 minutes; the blank is cooled with the furnace to obtain the blank; the prepared blank is surface ground and deburred to obtain high-entropy carbide-bonded polycrystalline cubic boron nitride.

[0010] Compared with the prior art, the present invention can achieve the following technical effects: The purpose of the present invention is to improve the high-temperature cutting hardness and thermal stability of PcBN, realize its long-term dry turning, improve the service life of the tool and the production efficiency of the enterprise, and provide a high-entropy carbide ceramic bonded polycrystalline cubic boron nitride and a preparation method thereof. The innovation of the present invention is to make it a PcBN binder with good thermal stability and superior performance by relying on the thermodynamic stability of high-entropy carbon ceramics and stable mechanical properties at high temperatures. DETAILED DESCRIPTION

[0011] Exemplary embodiments, features, and capabilities of the present invention will be described in detail below.

[0012] The invention discloses a high entropy carbide ceramic bonded polycrystalline cubic boron nitride, which is TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN 0.3 / TiB 1.8 / Al / ZrO2 is the binder, accounting for 5~20 vol.%, and the balance is cBN, accounting for 80~95 vol.%, with a particle size of 1~8 μm.

[0013] A method for preparing the above-mentioned high entropy carbide ceramic-bonded polycrystalline cubic boron nitride comprises the following steps: S1, binder powder TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN 0.3 / TiB 1.8 / Al / ZrO2 mechanical alloying, according to the transition metal in an equimolar ratio, weigh a total of 10 g of powder. The powder was ball-milled using a planetary ball mill. The ball mill and grinding balls were made of tungsten carbide, and the ball-to-material ratio was 20:1. Before ball milling, the weighed raw materials and grinding balls were placed in the ball mill in the argon atmosphere (99.99%, 0.5 MPa) of the glove box. The mass ratio of large, medium and small grinding balls was 5:3:2, and the diameters were 10 mm, 5 mm, and 1 mm, respectively. In the glove box, 1 ml of industrial alcohol was added to the powder as a dispersant, and the ball mill was sealed to fill it with argon atmosphere. The ball milling parameters were set as follows: speed 450 r / min; time 12 h.

[0014] S2. The high entropy carbide powder after mechanical alloying is mixed evenly with cBN in a volume ratio of 20~5%:80~95%. According to different cBN volume proportions of 95%, 90%, 85%, and 80%, the corresponding cBN particle sizes are 1μm, 2μm, 4μm, and 8μm, respectively. After the mixing is completed, pre-pressing is carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample is sintered at high temperature and high pressure. The sintering pressure is 6 GPa, the sintering temperature is 1500~1800 ℃, the holding time is 10 min, and then the temperature is reduced and the pressure is released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics. Example 1

[0015] The high entropy carbide binder powder after mechanical alloying was mixed evenly with cBN at a volume ratio of 20%:80%, and the added cBN particle size was 8 μm. After the mixing was completed, the pre-pressing was carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample was sintered at high temperature and high pressure. The sintering pressure was 6 GPa, the sintering temperature was 1500 ℃, the holding time was 10 min, and then the temperature was reduced and the pressure was released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0016] The polycrystalline cubic boron nitride sample after high pressure sintering was polished and then the microstructure and performance were tested. The Vickers hardness of the sintered block was 21.75 GPa and the fracture toughness was 6.1 MPa·m 1 / 2 . Example 2

[0017] The high entropy carbide binder powder after mechanical alloying was mixed evenly with cBN at a volume ratio of 15%:85%, and the added cBN particle size was 4 μm. After the mixing was completed, the pre-pressing was carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample was sintered at high temperature and high pressure. The sintering pressure was 6 GPa, the sintering temperature was 1500 ℃, the holding time was 10 min, and then the temperature was reduced and the pressure was released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0018] The polycrystalline cubic boron nitride sample after high pressure sintering was polished and then the microstructure and performance were tested. The Vickers hardness of the sintered block was 22.36 GPa and the fracture toughness was 7.41 MPa·m 1 / 2 . Example 3

[0019] The high entropy carbide binder powder after mechanical alloying was mixed evenly with cBN at a volume ratio of 15%:85%, and the added cBN particle size was 4 μm. After the mixing was completed, the pre-pressing was carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample was sintered at high temperature and high pressure. The sintering pressure was 6 GPa, the sintering temperature was 1600 ℃, the holding time was 10 min, and then the temperature was reduced and the pressure was released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0020] The polycrystalline cubic boron nitride sample after high pressure sintering was polished and then the microstructure and performance were tested. The Vickers hardness of the sintered block was 24.13 GPa and the fracture toughness was 8.53 MPa·m 1 / 2 . Example 4

[0021] The high entropy carbide binder powder after mechanical alloying was mixed evenly with cBN at a volume ratio of 15%:85%, and the added cBN particle size was 4 μm. After the mixing was completed, the pre-pressing was carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample was sintered at high temperature and high pressure. The sintering pressure was 6 GPa, the sintering temperature was 1700 ℃, the holding time was 10 min, and then the temperature was reduced and the pressure was released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0022] The polycrystalline cubic boron nitride sample after high pressure sintering was polished and then the microstructure and performance were tested. The Vickers hardness of the sintered block was 25.33 GPa and the fracture toughness was 8.33 MPa·m 1 / 2 . Example 5

[0023] The high entropy carbide binder powder after mechanical alloying was mixed evenly with cBN at a volume ratio of 15%:85%, and the added cBN particle size was 4 μm. After the mixing was completed, the pre-pressing was carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample was sintered at high temperature and high pressure. The sintering pressure was 6 GPa, the sintering temperature was 1800 ℃, the holding time was 10 min, and then the temperature was reduced and the pressure was released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0024] The polycrystalline cubic boron nitride sample after high pressure sintering was polished and then the microstructure and performance were tested. The Vickers hardness of the sintered block was 29.56 GPa and the fracture toughness was 8.53 MPa·m 1 / 2 . Example 6

[0025] The high entropy carbide binder powder after mechanical alloying was mixed evenly with cBN at a volume ratio of 10%:90%, and the added cBN particle size was 2 μm. After the mixing was completed, the pre-pressing was carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample was sintered at high temperature and high pressure. The sintering pressure was 6 GPa, the sintering temperature was 1600 ℃, the holding time was 10 min, and then the temperature was reduced and the pressure was released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0026] The polycrystalline cubic boron nitride sample after high pressure sintering was polished and then the microstructure and performance were tested. The Vickers hardness of the sintered block was 32.25 GPa and the fracture toughness was 9.1 MPa·m 1 / 2 . Example 7

[0027] The high entropy carbide binder powder after mechanical alloying was mixed evenly with cBN at a volume ratio of 5%:95%, and the added cBN particle size was 1 μm. After the mixing was completed, the pre-pressing was carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample was sintered at high temperature and high pressure. The sintering pressure was 6 GPa, the sintering temperature was 1600 ℃, the holding time was 10 min, and then the temperature was reduced and the pressure was released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

[0028] The polycrystalline cubic boron nitride sample after high pressure sintering was polished and then the microstructure and performance were tested. The Vickers hardness of the sintered block was 31 GPa and the fracture toughness was 8.15 MPa·m 1 / 2 .

[0029] It can be seen from Examples 1-7 that the innovation of the present invention is that the high entropy carbon ceramic becomes a PcBN binder with good thermal stability and superior performance by virtue of its thermodynamic stability and stable mechanical properties at high temperatures.

[0030] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A high entropy carbide-bonded polycrystalline cubic boron nitride, characterized in that: The high entropy ceramic binder powders TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN were prepared by using different cBN contents and cBN particle sizes. 0.3 / TiB 1.8 / Al / ZrO2 mixed sintering to prepare high entropy carbide ceramic bonded polycrystalline cubic boron nitride, wherein the mass percentage of the raw materials used in the preparation is: cBN accounts for 80-95 vol.% of the total mass, and the remainder is high entropy ceramic binder powder.

2. The high entropy carbide-bonded polycrystalline cubic boron nitride according to claim 1, characterized in that: High entropy ceramic binder powder TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN 0.3 / TiB 1.8 / Al / ZrO2 was synthesized by mechanical alloying with an equimolar ratio of transition metal atoms and a ball milling time of 12 h.

3. The high entropy carbide-bonded polycrystalline cubic boron nitride according to claim 1, characterized in that: The cBN particles have different cBN volume proportions of 95%, 90%, 85%, and 80%, and the corresponding cBN particle sizes added are 1μm, 2μm, 4μm, and 8μm, respectively.

4. A method for preparing high entropy carbide-bonded polycrystalline cubic boron nitride as claimed in any one of claims 1 to 3, characterized in that: It includes the following steps: S1, binder powder TiC / VC / ZrC / NbC / Mo2C / HfC / TaC / WC / TiN 0.3 / TiB 1.8 / Al / ZrO2 mechanical alloying, according to the transition metal in an equimolar ratio, weigh a total of 10 g of powder; the powder is ball-milled using a planetary ball mill, the ball mill and grinding balls are both made of tungsten carbide, the ball-to-material ratio is 20:1, before ball milling, the weighed raw materials and grinding balls are placed in the ball mill in the argon atmosphere (99.99%, 0.5 MPa) of the glove box; the mass ratio of large, medium and small grinding balls is 5:3:2, and the diameters are 10 mm, 5 mm, and 1 mm respectively; in the glove box, add 1 ml of industrial alcohol as a dispersant to the powder, seal the ball mill, and fill it with argon atmosphere. The ball milling parameters are set as follows: speed 450 r / min; time 12 h; S2. The high entropy carbide powder after mechanical alloying is mixed evenly with cBN in a volume ratio of 20~5%:80~95%. According to different cBN volume proportions of 95%, 90%, 85%, and 80%, the corresponding cBN particle sizes are 1μm, 2μm, 4μm, and 8μm respectively. After the mixing is completed, pre-pressing is carried out with a pressure of 400 MPa and a holding time of 100 s; then, the pre-pressed sample is sintered at high temperature and high pressure; the sintering pressure is 6 GPa, the sintering temperature is 1500~1800 ℃, the holding time is 10 min, and then the temperature is reduced and the pressure is released to prepare polycrystalline cubic boron nitride bonded with high entropy carbide ceramics.

5. The method for preparing high entropy carbide-bonded polycrystalline cubic boron nitride according to claim 4, characterized in that: According to different cBN volume proportions of 95%, 90%, 85%, and 80%, and different sintering temperatures of 1500~1800 ℃, the hardness of the obtained polycrystalline cubic boron nitride is 21~33 GPa, and the fracture toughness is: 6~9.1 MPa·m 1 / 2 .

6. The method for preparing high entropy carbide-bonded polycrystalline cubic boron nitride according to claim 4, characterized in that: First, a pressure of 6 GPa is slowly applied to the sample within 1 minute; then the temperature is raised to 1500-1800 °C and kept at this temperature for 10 minutes; the blank is cooled with the furnace to obtain the blank; the prepared blank is subjected to surface grinding and deburring treatment to obtain high-entropy carbide-bonded polycrystalline cubic boron nitride.

Citation Information

Patent Citations

  • Method for preparing polycrystalline diamond through using nano-onion carbon and micron order diamond

    CN103274398A